Wisconsin "goverment and business" and the history of heterodox economic thought - Samuels, Warren J. (Amsterdam; London Elsevier, 2004)
The volume contains two groups of archival materials. One group includes notes from courses given at the University of Wisconsin by Edwin E. Witte and Robert Lampman on the economic role of government. The second group includes papers from a conference on the history of 20th century heterodox economics
Includes bibliographical references.
rpm 27/08/13
Loan
Keywords: Economics -- History; Economics -- Methodology -- History